Load-bearing Behaviour of Laminated Tempered Glass with Reground Edges - Maximilian Möckel (Challenging Glass Conference, 2020)
Designers use exposed glass edges to reach maximum transparency, for example within glass steps, glass beams or glass columns. These applications require mechanical finishing to achieve high optical quality and to compensate for the edge notch that results from the manufacturing process of safety glass. Regrinding of annealed glass is allowed without restrictions. In the case of glass with load bearing functions, tempered glass, heat-strengthened glass or fully tempered glass, is required. However, a risk of premature failure occurs when regrinding tempered glass because of a reduction of the compression zone at the edge.